Crampology: pathophysiology and diagnosis of muscle cramps - Katzberg, Hans (Henry Stewart Talks, 2023)
Neurogenic muscle cramps, Myopathic muscle cramps, Cramp electromyographic, Cramp potentials and after-discharges, Who suffers from muscle cramps?, Muscle cramps and metabolic disruption, Muscle cramps and diabetes, Cramp fasciculation syndrome/voltage-gated K+ channelopathy